Study on effect demand side management and penalty assessment based on guaranteed standard performance on reliability performance of distribution network - Muhamad Haziq, Mohd Khairi Azahar; Nurul Najihah, Azizan; Mohd Ikhwan, Muhammad Ridzuan (Institution of Engineering and Technology, 2022)
The distribution network is an essential component of strategic planning because it assures that power is delivered to consumers without interruption and with high reliability. In such an operation, the demand is met by adjusting the generated power, and then the power system's safe performance is achieved. Besides that, nowadays, reliability performance of power supply systems is a crucial priority for distribution network operators (DNOs). In a certain period of years, Energy Regulators revises their performance requirement limits for more reliability and continuity of supply service to the customer and correspondingly, penalties applied to each DNO based on the achieved network performance. However, in recent years, a new idea in electric power networks has emerged: demand side management (DSM). DSM is the process of influencing consumer energy demand via a variety of means, including financial incentives and education. The purpose of DSM is usually to persuade consumers to use less energy during peak hours or to shift their energy use to off-peak periods like nights and weekends. Interruptible loads are one of DSM's most important models. Three cases of reliability evaluation of distribution systems using Monte Carlo simulation (MCS) will be explored in this study. In the first case, no DSM and penalty approach was included in the process, and the reliability calculation considered each customer's peak load. In the second case the DSM is considered, and the changes in system load are represented by the load profile throughout the day. For the third case the DSM and penalty will assess and evaluate the efficiency of reliability performance. The simulation results demonstrate that interruptible loads have a significant impact on power system reliability.